Bud and Leaf Diseases of Some Woody Plants in Some Private and Public Nurseries of Istanbul - (:unkn) unknown (My University, 2018)
This study was carried out between the years 2007-2008 and 2017-2018, embraces a number private and publicnurseries including those in the Municipality of Istanbul and some of the local administrations, as well asadministered by the Ministry of Forestry. 91 types of infectious disease factors have been determined in thenurseries. The study, conducted in four seasons, has revealed various plant diseases such as anthracnose, fungusblight, corrosion and decomposition, respectively. Despite being few in numbers, five different diseases relatedto 11 bacteria and three types of virus were also seen. Besides the infectious diseases, 5 types of non-infectiousdiseases on 11 plants were discovered.

Bu çalışma, 2007-2008 ve 2017-2018 yılları arasında İstanbul Belediyesi ve Orman Bakanlığı tarafından yönetilen özel ve halk fidanlıklarında yürütülmüştür. Fidanlıklarda 91 bulaşıcı hastalık etmeni tespit edilmiştir. Dört mevsim boyunca yürütülen çalışma antraknoz, mantar yanıklığı, korozyon ve çürüme gibi çeşitli bitki hastalıklarının varlığını ortaya çıkarmıştır. Sayıları az olmasına rağmen 11 bakteri ile ilişkili beş farklı hastalık ve üç tip virus de görülmüştür. Bulaşıcı hastalıkların yanında 11 bitkide bulaşıcı olmayan beş hastalık tipi ortaya konmuştur
İstanbul’un Bazı Özel ve Halk Fidanlıklarındaki Bazı Odunsu Bitkilerin Dal ve Yaprak Hastalıkları
Keywords: Biyoloji; Matematik; İnşaat ve Yapı Teknolojisi; İnşaat Mühendisliği; Mühendislik, Elektrik ve Elektronik; Mühendislik, Makine